Interoganizational utility of welfare stigma in the criminal justice system - Lara-Millán, Armando (Criminology, 2017)
The appropriation of “welfare stigma” or stereotypes about poor people's overreliance and abuse of public aid in two core criminal justice functions is examined: felony adjudication in a court system and space allocation in a jail. Through a comparative ethnographic study in which an abductive analysis of data (20 months of fieldwork) was used, we show that criminal justice gatekeepers utilize welfare stigma to create stricter eligibility criteria for due process in criminal courts and occupancy in jails. Specifically, the number of court appearances, motions, trials, jail beds, food, showers, and medical services is considered by professionals to be the benefits that individuals seek to access and abuse. Professionals view their role as preventing (rather than granting) access to these resources. The comparative nature of our data reveals that welfare stigma has interorganizational utility by serving two different organizational goals: It streamlines convictions in courts, which pulls defendants through adjudication, and conversely, it expands early release from jails, which pulls inmates out of the custody population. In the context of diminishing social safety nets, our findings have implications for understanding how discretion is exercised in an American criminal justice system increasingly tasked with the distribution of social services to the urban poor.